Ustalenie danych osobowych sprawcy naruszenia dóbr osobistych w Internecie celem dochodzenia ich ochrony w postępowaniu cywilnym - Piesiewicz, Piotr; Piaskowska, Olga (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The subject of the considerations taken up by the authors in this article is the legal issues related to the possibility of pursuing a claim for infringement of personal rights on the Internet from the direct infringer through the prism of necessity to establish the personal data of the infringer unknown. The possibility of submitting an application for making this data available to the service provider was discussed, taking into account both the position expressed by the Court of Justice of the European Union and the national administrative courts. Attention was drawn to the fact that the difficulty in establishing these data (in accordance with the provisions of the Act of 18 July 2002 on the provision of electronic services) results in an incorrect practice of initiating criminal proceedings, which in turn causes the investigative authorities to be burdened with tasks that do not serve the purposes of the criminal trial but in fact civil cases.